Potential of rice industry biomass as a renewable energy source - Mofijur M.; Mahlia T.M.I.; Logeswaran J.; Anwar M.; Silitonga A.S.; Rahman S.M.A.; Shamsuddin A.H. (MDPI AG, 2023)
Alternative fuels; Biomass; Coal combustion; Coal transportation; Cost effectiveness; Fossil fuel power plants; Fossil fuels; Gasification; Power generation; Waste incineration; Fossil-fuel depletions; Impact on the environment; Renewable energies; Renewable energy source; Rice husk; Rice straws; Transportation cost; Waste management systems; Waste management